2012
DOI: 10.1080/0886571x.2012.702519
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma Experience and the Expression of Problematic Sexual Behavior in Children and Adolescents in State Custody

Abstract: The present study is designed to identify which types of trauma experiences interact with later development of normal and abnormal sexual behavior in children and adolescents. More specifically, our goal is to determine which types of trauma exposure are related to issues of sexuality, sexually reactive behavior, sexually aggressive behavior, and the combination of both sexually reactive and sexually aggressive behavior. A sample of 5,976 children ages 5 to 18 who were wards of the State of Illinois were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
1
19
1
5
Order By: Relevance
“…The high number of multiple maltreatment experiences likely reflect a history of more maltreatment reports and/or more polyvictimization, which have been found to result in trauma symptomotology[22] Our findings are similar to a study of youth in foster care which found that multiple trauma experiences increased the likelihood of risky sexual behaviors[23]. Sexual risk behavior prevention education may be less effective when youth have complex trauma as a result of childhood maltreatment, as complex trauma affects the youth's emotional responses, relationships, behavior, as well as health outcomes[24].…”
Section: Discussionsupporting
confidence: 74%
“…The high number of multiple maltreatment experiences likely reflect a history of more maltreatment reports and/or more polyvictimization, which have been found to result in trauma symptomotology[22] Our findings are similar to a study of youth in foster care which found that multiple trauma experiences increased the likelihood of risky sexual behaviors[23]. Sexual risk behavior prevention education may be less effective when youth have complex trauma as a result of childhood maltreatment, as complex trauma affects the youth's emotional responses, relationships, behavior, as well as health outcomes[24].…”
Section: Discussionsupporting
confidence: 74%
“…Research also indicated youths' psychosocial health, experiences of trauma or neglect, and relationships with adults in their lives significantly affect sexual choices and health outcomes (Cunningham, Martinez, Scott-Sheldon, Carey, & Carey, 2017;DiIorio, Pluhar, & Belcher, 2003;Szanto, Lyons, & Kisiel, 2012), emphasizing the importance of social experiences.…”
Section: Research Supportmentioning
confidence: 99%
“…Puisqu'il n'existe aucune définition opérationnelle claire des CSP à l'heure actuelle (Lepage, Tourigny, Pauzé, McDuff et Cyr, 2010;Szanto, Lyons et Kisiel, 2012), il n'y a pas de limite précisant le moment à partir duquel un comportement sexuel, en apparence anodin, doit être considéré comme anormal ou malsain (Johnson, 2002). Cette distinction est d'autant plus difficile à faire qu'elle s'appuie généralement sur des considérations normatives (âge et stade de développement de l'enfant) (Szanto, Lyons et Kisiel, 2012) et culturelles (Chaffin, Letourneau et Silovsky, 2002).…”
Section: à Partir De Quand Peut-on Parler De Comportements Sexuels Prunclassified
“…Puisqu'il n'existe aucune définition opérationnelle claire des CSP à l'heure actuelle (Lepage, Tourigny, Pauzé, McDuff et Cyr, 2010;Szanto, Lyons et Kisiel, 2012), il n'y a pas de limite précisant le moment à partir duquel un comportement sexuel, en apparence anodin, doit être considéré comme anormal ou malsain (Johnson, 2002). Cette distinction est d'autant plus difficile à faire qu'elle s'appuie généralement sur des considérations normatives (âge et stade de développement de l'enfant) (Szanto, Lyons et Kisiel, 2012) et culturelles (Chaffin, Letourneau et Silovsky, 2002). Selon plusieurs experts (Araji, 1997;Chaffin et al, 2006;Hall, Mathews et Pearce, 1998;Johnson, 2004), différents indicateurs devraient être considérés pour juger du caractère problématique des comportements sexuels : a) ils surviennent à une fréquence élevée; b) ils sont devenus une préoccupation importante pour l'enfant; c) ils persistent malgré l'intervention d'un adulte; d) ils surviennent entre des enfants d'âge, de taille ou de stade développemental différents; e) ils se manifestent par le recours à la force, à la coercition ou à l'intimidation; f) ils sont associés à une détresse émotionnelle chez l'enfant (les enfants) impliqué(s); g) ils interfèrent dans le développement social de l'enfant (des enfants); ou h) ils entraînent des blessures physiques.…”
Section: à Partir De Quand Peut-on Parler De Comportements Sexuels Prunclassified